Functional imaging of the hemodynamic sensory gating response in schizophrenia. Issue 9 (28th March 2012) - Mayer, Andrew R.; Ruhl, David; Merideth, Flannery; Ling, Josef; Hanlon, Faith M.; Bustillo, Juan; Cañive, Jose
<x xml:space="preserve">Abstract</x> The cortical (auditory and prefrontal) and/or subcortical (thalamic and hippocampal) generators of abnormal electrophysiological responses during sensory gating remain actively debated in the schizophrenia literature. Functional magnetic resonance imaging has the spatial resolution for disambiguating deep or simultaneous sources but has been relatively under‐utilized to investigate generators of the gating response. Thirty patients with chronic schizophrenia (SP) and 30 matched controls participated in the current experiment. Hemodynamic response functions (HRFs) for single (S1) and pairs (S1 + S2) of identical ("gating‐out" redundant information) or nonidentical ("gating‐in" novel information) tones were generated through deconvolution. Increased or prolonged activation for patients in conjunction with deactivation for controls was observed within auditory cortex, prefrontal cortex, and thalamus in response to single tones during the late hemodynamic response, and these group differences were not associated with clinical or cognitive symptomatology. Although patient hyperactivation to paired‐tones conditions was present in several regions of interest, the effects were not statistically significant for either the gating‐out or gating‐in conditions. Finally, abnormalities in the postundershoot of the auditory HRF were also observed for both single and paired‐tones conditions in patients. In conclusion, the amalgamation of the entire electrophysiological response to both S1 and S2 stimuli may limit hemodynamic sensitivity to paired tones during sensory gating, which may be more readily overcome by paradigms that use multiple stimuli rather than pairs. Patient hyperactivation following single tones is suggestive of deficits in basic inhibition, neurovascular abnormalities, or a combination of both factors. Hum Brain Mapp 34:2302–2312, 2013. © 2012 Wiley Periodicals, Inc.